Tailor-made organosolv lignins from coconut wastes: Effects of green solvents in microwave-assisted processes upon their structure and antioxidant activities. (September 2019) - Avelino, Francisco; Silva, Kássia T.; Mazzetto, Selma E.; Lomonaco, Diego
Abstract: Organosolv processes have been applied for obtainment of high quality lignin, allowing the utilization of different reaction conditions. Our aim was to evaluate the differences between lignins obtained from coconut shell under acetosolv (ACSL) and formosolv (FCSL) processes and assess their antioxidant activities. ACSL and FCSL were obtained using acetic or formic acids co-catalyzed by AlCl3, H2 SO4 or HCl. Structural characterizations were performed using spectroscopic, chromatographic and thermo-analytical methods, while antioxidant capacities were evaluated by DPPH assay. The main difference observed was the partial acylation of ACSLs, not observed in FCSLs. These structural features influenced their glass transition temperatures and antioxidant capacities. ACSL presented lower T g and higher IC50 values than FCSL, but both lignins had lower IC50 than commercial antioxidants. As conclusion, the use of specific organosolv processes has great potential for the selective production of lignins with specific functionalities and processability, very useful for further technological applications. Graphical abstract: Unlabelled Image Highlights: Acetosolv and formosolv processes were carried out under mild conditions. Partial acetylation of aliphatic hydroxyls of ACSLs occurred in a one pot process. Microwave-assisted organosolv process can promote selective chemical modifications. Formosolv lignins had lower IC50 values than those of ACSLs. Organosolv lignins had lower IC50 values than those of BHT and Irganox 1010.